Metabolomic Comparison of Patients With Colorectal Cancer at Different Anticancer Treatment Stages - Li, Zhuofei; Deng, Xingming; Luo, Jun; Lei, Yunpeng; Jin, Xinghan; Zhu, Jing; Lv, Guoqing (Frontiers in Oncology, 2022)
Backgrounds: The difficulties of early diagnosis of colorectal cancer (CRC) result in tis high mortality rate. The ability to predict a patient's response to surgical resection or chemotherapy, may be of great value for clinicians to arrange CRC treatments. Metabolomics is an emerging tool for biomarker discovery in cancer research. Previous reports have indicated that metabolic profile of individuals can be significantly altered between CRC patients and healthy controls. However, the metabolic changes of CRC patients at different treatment stages has not been explored. Methods: To this end, we have performed nuclear magnetic resonance (NMR)-based metabolomic analysis to determine the metabolite aberrations in CRC patients before and after surgical resection or chemotherapy. In general, a total of 106 urine samples from four clinical groups, including healthy volunteers (n=31), pre-surgery CRC patients (n=25), post-surgery CRC patients (n=25), post-chemotherapy CRC patients (n=25) were collected and subjected for further analysis. Results: In this present study, we identified five candidate metabolites nominated as N-phenylacetylglycine, succinate, 4-hydroxyphenylacetate, acetate and arabinose, in CRC patients compared with healthy individuals, in which three of them were firstly reported. Furthermore, approximately ten metabolites were uniquely identified at each stage of CRC treatment, serving as good candidates for biomarker panel selection. Conclusion: In summary, these potential metabolites candidates may provide promising early diagnostic and monitoring approaches for CRC patients at different anti-cancer treatment stages.